The effect of undercooling on the microstructure and tensile properties of hypoeutectic Sn–6.5Zn–xCu Pb-free solders. (5th September 2015) - El-Daly, A.A.; Desoky, W.M.; Saad, A.F.; Mansor, N.A.; Lotfy, E.H.; Abd-Elmoniem, H.M.; Hashem, H.
Graphical abstract: Highlights: Small amounts of Cu have been added into Sn–6.5Zn solder alloy. A new type of flower-like γ-Cu5 Zn8 IMC was detected with Cu addition. The shape and size of flower-like IMCs control the overall Sn–6.5Zn properties. Optimal percentage of Cu was 0.5% Cu to enhance the overall properties. 1.5% Cu addition induced undesirable effects on Sn–6.5Zn properties. Abstract: Hypoeutectic Sn–6.5Zn alloy may be regarded as a better choice than eutectic Sn–9Zn lead-free solder in microelectronics industry. In this study, the properties of hypoeutectic Sn–6.5Zn lead-free solder were modified with minor additions of Cu. SEM investigations reveal that the plain Sn–6.5Zn solder exhibits large number of undesirable acicular structure of angular needle-like Zn particles at the solder matrix. The acicular-shape morphology of Zn was remarkably suppressed after Cu modification. Moreover, a new type of small flower-like γ-Cu5 Zn8 intermetallic compound (IMC) was detected with 0.5 wt.% Cu added specimens. The flower-like morphology of γ-Cu5 Zn8 IMC appears to cause a sharp increase in Young's modulus, yield strength (YS) and ultimate tensile strength (UTS) of Cu modified solder. However, this effectiveness is reduced when 1.5 wt.% Cu addition starts to enhance the growth of coarse dendrite morphology of γ-Cu5 Zn8 phase with enlarged β-Sn matrix. In addition, a 1.5 wt.% Cu addition was found to induce undesirable effects on the degree of undercooling, melting temperature and pasty range. Constitutive Garofalo model was assembled based on the experimental data of Sn–6.5Zn lead-free solders.